Upaya Pengembangan Pantai Alam Geger sebagai Objek Wisata dalam Meningkatkan Tourism Visit dan Economic Sector bagi Masyarakat Desa Kampung dalam Kabupaten Labuhan Batu - Surya Dharma Susilo; Elida Florentina Sinaga Simanjorang; Nurintan Asyiah Siregar (Universitas Medan Area, 2022)
Alam Geger Beach is located in Kampung Dalam Village, Labuhanbatu Regency. Formerly this location was a small river that was very clear, stretching between oil palm plantations owned by a farmer named H. Ahmat Syarif Nasution. In the last two years (2019-2021) when the world was hit by the Covid-19 virus pandemic, including Indonesia, the economy stagnates. This gave rise to an idea to manage the flow of the river to become a tourist attraction. The purpose of this service is to develop Alam Geger Beach as a tourist attraction in increasing tourist visits and improving the economic sector for the people of Kampung Dalam Village, Labuhanbatu Regency. The method of this service uses the SWOT and participatory analysis method which is carried out by the author through several stages of activities. The results of this service activity are making several facilities and infrastructure to support the development of Alam Geger Beach tourism and introducing this tourist attraction through social media, so that there is a significant increase in the number of visitors who come. There has also been an increase in the economic sector for the village community around the tourist attraction through the sale of food and beverages, although this is less significant. Therefore, further observation is needed, cooperation with culinary entrepreneurs and attention from the Labuhanbatu Regency government to make it happen.